Komunikasi Pemberdayaan sebagai Perspektif Baru Pengembangan Pendidikan Komunikasi Pembangunan di Indonesia - Yuli Setyowati (Institut Pertanian Bogor, 2019)
The presence of development communication is basically aimed at contributing to the development process, especially in order to accelerate the diffusion process of innovation. The diffusion of innovation in development is an effort to meet the demands of modernization. Therefore, development is often equated with the term modernization. One indicator of modernization is the presence of communication technology that is very fast developing. Communication technology that was created to facilitate human work in the end was not able to place humans as subjects, but instead became the object of technology. The helplessness of individual humans when dealing with communication technology is a picture of the failure of the development process and human-centered social change. Communities are often powerless to stem the hegemony of communication technology. Therefore empowerment communication is a new perspective in the education of development communication in the spirit of voicing the voiceless. This study aims to reveal the social changes that occur in the